Negotiating Intra-Muslim Difference in Indonesian Lived Islam: Religious Authority, Islamic Organizations, and The Sunni–Shia Question - Rifqa Rifqa; Isman Iskandar; Andrew Hari Yoga; Riski Suriani Lubis (JURNAL INDO-ISLAMIKA, 2026)
This article examines the Sunni–Shia question in Indonesia as a site for understanding how intra-Muslim difference is negotiated within Indonesian lived Islam. Rather than treating Sunni–Shia tension merely as a theological or sectarian conflict, the study situates it within broader transformations of religious authority, institutional discourse, public morality, and everyday Muslim social life. The article aims to analyze how three major Islamic organizations the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah construct, mediate, and recontextualize religious authority in responding to Sunni–Shia difference. Methodologically, the study employs a qualitative documentary case study approach, drawing on official fatwas, organizational statements, institutional publications, human rights reports, and relevant scholarly literature. The data are analyzed through qualitative content analysis and thematic interpretation, guided by the concepts of lived religion, religious authority, and Muslim politics. The findings show that MUI represents a normative-regulative model of authority through fatwa and doctrinal boundary-making; NU represents a cultural-mediative model through pesantren networks, kiai authority, and the ethics of ukhuwah and tasāmuḥ; while Muhammadiyah represents an educational-civic model through religious moderation, Islamic education, public reasoning, and Islam Berkemajuan. The article argues that Indonesian Islamic authority is plural, layered, and context-dependent. Its main contribution lies in reframing the Sunni–Shia question not as a marginal sectarian issue, but as a critical lens for understanding how lived Islam is transformed through competing yet interconnected forms of religious authority.